Aspirant candidate behaviour and progressive political ambition. (February 2017) - Allen, Peter; Cutts, David
In this paper we take account of the role of aspirant candidate behaviour in progressive political ambition, specifically how some individuals signal their political ambition to political actors by approaching them to discuss running for office. We examine how the effect of this behaviour compares to the more prominently studied effect of elite recruitment. We conclude that signalling behaviour by an aspirant candidate has a substantial effect, particularly with regard to actually acting on initial considerations of whether to stand, and that elite recruitment makes a difference but only in conjunction with the aspirant candidate themselves signalling their ambition to political actors.